Pengaruh diameter lubang bubbles generator pada pengikatan karbon dioksida dengan larutan kalium hidroksida 4 molar - Bachrudin, M.N.; Sutjahjono, H.; Ramadhan, M.E. (Dinamika Teknik Mesin, 2018)
Bubble generator is an alternative technology for bubble producers. One of many other functions of bubble generator is as a purification tool. Type of bubble generator that's used in this research is Jet Column bubble generator. The diameter of the bubble hole generator affects the length of bubble life, the length of the bubble trajectory, the bubble shape, and the purification process absorption of CO2. The methods used in the purification process are making a solution 4 KOH molar, making purification tool, installating the output holes, gas purification process and gas testing performed repeated three times in each test process. The output bubble generator hole diameters are 0.08 mm, 0.12 mm and 0.16 mm. The result shows that the greater the diameter of the bubble hole generator of 0.12 mm makes the length of bubble life shorter, the time is 1,77 s and for the smallest hole diameter of 0.08 mm makes the length of the bubble life af about 3.21 s. The hole diameter of 0.08 mm results in the length of bubble trajectory of 1554.289 mm that is  longer than that of the hole diameter of 0.16 mm. The smaller hole diameter produces bubbles with an average length of 6.441 mm and bubble diameter of 1.237 mm. CO2 gas content decreased from 26.8% to 0.00%, and levels of hydrocarbon content increased by 5540 ppm.